The Effect of Tokopedia Application Features and User Experience on The Ease of The Digital Payment System (E-Wallet Integration) on Tokopedia Purchases - Reza Febrian Nur Rizki; Rahmadi (Rescollacom (Research Collaborations Community), 2026)
The development of digital payment systems in e-commerce platforms has emphasized the importance of ease of transactions for users. As one of the largest e-commerce platforms in Indonesia, Tokopedia has enhanced customer convenience by integrating various e-wallet-based digital payment features. The purpose of this study is to examine how application features and user experience impact the ease of digital payment systems, also known as e-wallet integration. This study employed a quantitative and associative approach. Data were obtained through purposive sampling by distributing questionnaires to 150 selected Tokopedia application users. Data analysis was performed using multiple linear regression analysis using SPSS. The results showed that application features had a positive and significant effect on the ease of digital payment systems. In addition, user experience also had a positive and significant effect on the ease of digital payment systems, with a coefficient of determination of 66.1%. These results indicate that improving the quality of application features improves the ease of digital payment systems. It is hoped that this research will help e-commerce platform managers develop application features and designs that focus on user convenience and comfort.